Participatory Evaluation of a Direct Payment Program for Equity in Dementia Care in Nova Scotia, Canada: A Study Protocol - Emily Reid-Musson PhD; Katie Aubrecht PhD; Christine Kelly PhD; Mark G. Embrett PhD; Lars K. Hallstrom PhD; Barbara Hamilton-Hinch PhD; Shanthi Johnson PhD, RD, FDC, FACSM, FGSA; Shala Knocton MSc; Logan Lawrence PhD; Marilyn MacDonald PhD; Jasmine Mah MD; Patrik Marier PhD; et al. (International Journal of Qualitative Methods, 2023)
Nova Scotia's Supportive Care Program (SCP) is an individualized funding program that provides funds for people living with dementia (PLWD) or acquired brain injuries to purchase basic home care services such as personal care, respite, cleaning and cooking. The SCP has the potential to address the Quintuple Aim of enhancing care experience, improving population health, reducing costs, improving provider experience and improving health equity, yet qualitative evidence is lacking. The aim of this study is to use participatory program evaluation methods to evaluate the SCP and consider how effective it is in addressing the Quintuple Aim. The study objectives and corresponding methods are to (1) Co-develop a SCP logic model to guide the evaluation through consultations with a diverse group of stakeholders including PLWD, caregivers, care providers, researchers, government representatives, and nongovernment organizations, with attention to gender; (2) Evaluate the SCP based on the outcomes and outputs identified in the logic model using focus groups with PLWD, caregivers and home care providers, and interviews with PLWD and their caregivers; and (3) Mobilize knowledge about the ways the SCP addresses the Quintuple Aim through integrated knowledge translation activities with public, policy and research audiences. By focusing on clinically and socially vulnerable populations of PLWD and caregivers, the proposed evaluation of the SCP offers a valuable case in assessing the effectiveness of individually-funded home care in addressing the Quintuple Aim including health equity within the context of dementia care.